Social Representation of Nursing care in Mental Health: qualitative study - Macedo, Jaqueline Queiroz de; Silveira, Maria de Fatima Araújo; Eulálio, Maria do Carmo; Fraga, Maria Nazaré O.; Braga, Violante Augusta Batista (Online Brazilian Journal of Nursing, 2011)
<!–[endif]–><!–[endif]–>